Hubungan Motivasi Kerja dengan Kinerja Guru SMP Negeri 3 Suruh - Annan, Fikri Syahnakri; Tagela, Umbu; Windrawanto, Yustinus (Journal Prakarsa Paedagogia, 2023)
This study aims to determine the significance of the relationship between work motivation and teacher performance at SMP Negeri 3 Suruh, Semarang Regency. The type used in this research is correlational research. The sampling technique used in this research is technique total sampling  by taking as many as 30 teachers according to the population. The data in this study were taken using a scale technique with 4 alternative answers. The data obtained will then be analyzed using correlation techniques kendall’s tau-b with the help of programs IBM Statistics SPSS 25. The results showed that a correlation coefficient of 0.587** was obtained and a significance value of 0.000 (0.01). These results indicate that there is a significant relationship between work motivation and teacher performance at SMP Negeri 3 Suruh, Semarang Regency.